2000
DOI: 10.4269/ajtmh.2000.62.524
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of artemotil (beta-arteether) in Zambian children with cerebral malaria.

Abstract: Abstract. The efficacy and safety of intramuscular artemotil (ARTECEF ) was compared to intravenous quinine in African children with cerebral malaria. This prospective block randomized open-label study was conducted at two centers in Zambia. Subjects were children aged 0 to 10 years of age with cerebral malaria and a Blantyre Coma Score of 2 or less. Ninety two children were studied; 48 received artemotil and 44 quinine. No significant differences in survival, coma resolution time, neurologic sequelae, parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 27 publications
1
21
1
Order By: Relevance
“…9,58 The results contributed to a low therapeutic potential of intramuscular AE when compared with oral DQHS, oral and intravenous artesunate (AS), intramuscular AM, and even intramuscular ␣/␤-AE formulated with peanut oil in humans. 9,[59][60][61] Although far fewer undesirable side effects were reported in these trials, the lower efficacy limited the use of the drug in patients infected with P. falciparum malarias. Previous PK data demonstrated that the AM plasma concentration was more than three-fold higher than that of AE in rats at a same dose level and with the same sesame oil formulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,58 The results contributed to a low therapeutic potential of intramuscular AE when compared with oral DQHS, oral and intravenous artesunate (AS), intramuscular AM, and even intramuscular ␣/␤-AE formulated with peanut oil in humans. 9,[59][60][61] Although far fewer undesirable side effects were reported in these trials, the lower efficacy limited the use of the drug in patients infected with P. falciparum malarias. Previous PK data demonstrated that the AM plasma concentration was more than three-fold higher than that of AE in rats at a same dose level and with the same sesame oil formulation.…”
Section: Resultsmentioning
confidence: 99%
“…20 It may be that AM has a less lipophilic property than AE that favors absorption from muscle. Better efficacy of ␣/␤-AE was found in a peanut oil formulation in India, [59][60][61] suggesting that peanut oil may also facilitate better absorption of this drug in humans. Therefore, further investigation on new intramuscular formulations needs to be done to increase efficacy and decrease toxicity of the oil-soluble antimalarial drug AE.…”
Section: Resultsmentioning
confidence: 99%
“…The trials examined mortality, clinical outcomes (fever clearance time, coma recovery time, neurological sequelae), parasite clearance and some side effects. (Table II) was low for three trials (11,12,14), moderate for another three (8,10,17) and high for four trials (9,13,15,16). Only one trial(11) provided a sample size calculation.…”
Section: Current Best Evidencementioning
confidence: 96%
“…Table I summarizes the trial characteristics. Two trials compared quinine with artesunate (8,9), six with artemether(10-15), and two with arteether (16,17). Four trials recruited only participants with cerebral malaria (10,11,13,14).…”
Section: Current Best Evidencementioning
confidence: 98%
“…3 days) [14,[19][20][21] . ␤ AE formulated in sesame oil by the WHO [31,32] for higher-dose injections (total dose: 576-768 mg, i.m., in 5 days) has been reported to produce much lower cure rates [33,34] . AE ( ␣ / ␤ ) has been claimed to exhibit synergistic action [35,36] .…”
Section: Discussionmentioning
confidence: 99%